Geochronology of the Late Cretaceous magmatisni and metamorphism, Pütürge massif, Turkey - Kilig, Ayse Didem; Ates, Cihat (Science Press, 2015)
The Piitiirge massif was developed within the south branch of Neotethys, and it is possibly one of the terranes within the Late Cretaceous eollisional zone between the Eurasia and Arabian plates. Regional metamorphic rocks of the Piitiirge massif mainly include metapelitic schist, metapelitie gneiss, granitic gneiss, quartzite, amphibolite and marble. A Barrovian-like prograde sequence is found in the metapelites in this terrane, and metamorphic peak of this massif reached upper greenschist to amphibolite facies conditions. SIMS U-Pb age of 84. 2 ± 1. IMa of the zircons was obtained from the metagranitic gneiss of the Piitiirge massif suggests that the magmatism occurred at the Upper Cretaceous Santonian time, and 40Ar/39Ar age of the biotites separated from the metapelitic schist was determined to be 83. 21 ± 0. 069Ma. These geochronological data suggest that the metamorphism occurred immediately after the magmatism. © 2015 Science Press. All rights reserved.
????ü?ü??????????????????????????
Keywords: 40Ar/39Ar age; Neotethys evolution; Piitiirge metamorphic massif; Turkey; U-Pb age